U6 small nuclear RNA is transcribed by RNA polymerase III. - Kunkel, G R (1986)
A DNA fragment homologous to U6 small nuclear RNA was isolated from a human genomic library and sequenced. The immediate 5'-flanking region of the U6 DNA clone had significant homology with a potential mouse U6 gene, including a "TATA box" at a position 26-29 nucleotides upstream from the transcription start site. Although this sequence element is characteristic of RNA polymerase II promoters, the U6 gene also contained a polymerase III "box A" intragenic control region and a typical run of five thymines at the 3' terminus (noncoding strand). The human U6 DNA clone was accurately transcribed in a HeLa cell S100 extract lacking polymerase II activity. U6 RNA transcription in the S100 extract was resistant to alpha-amanitin at 1 microgram/ml but was completely inhibited at 200 micrograms/ml. A comparison of fingerprints of the in vitro transcript and of U6 RNA synthesized in vivo revealed sequence congruence. U6 RNA synthesis in isolated HeLa cell nuclei also displayed low sensitivity to alpha-amanitin, in contrast to U1 and U2 RNA transcription, which was inhibited greater than 90% at 1 microgram/ml. In addition, U6 RNA synthesized in isolated nuclei was efficiently immunoprecipitated by an antibody against the La antigen, a protein known to bind most other RNA polymerase III transcripts. These results establish that, in contrast to the polymerase II-directed transcription of mammalian genes for U1-U5 small nuclear RNAs, human U6 RNA is transcribed by RNA polymerase III.